0126 Trainees consider endovenous simulators to be realistic. (2nd November 2015) - Bamford, Richard; Chinai, Natasha; Coulston, James; Stewart, Andrew
Abstract : Background: Restrictions on surgical trainee time and access to procedures limit the opportunities trainees have to develop surgical skills. Simulated models can be highly beneficial to help develop individual surgical techniques. Endovenous therapy requires a unique skill set to be acquired by a trainee. We aim to identify how realistic trainees find an endovenous simulator. Method: All vascular trainees within a training region were invited to attend an endovenous training day using phantom limb simulators. Trainees were asked to complete a questionnaire reflecting their opinions on the realism of the simulators used with a 5 point Likert Scale. A phantom Limb Simulator and simulated vein pads were used during the course with real time ultrasound. Results: Seventy five per cent (6/8) of vascular trainees within the region attended the course. Of those, none had been involved in more than 30 endovenous cases and two had been involved in more than 20. 5/6 (83%) agreed or strongly agreed that the simulator was realistic for venous access. 4/6 (66.7%) agreed or strongly agreed that the phantom limb model was realistic for endovenous laser treatment and radiofrequency techniques including catheter insertion and placement and injection of tumerescence. Conclusion: These data suggest that trainees find phantom limb simulators to be a realistic method of training in endovenous techniques and they could be used to aid training. References: Sutherland LM, Middleton PF, Anthony A, et al . Surgical simulation: systematic review. Ann Surg. 2006;243:291–300 Dutta S, Gaba D, Krummel TM. To simulate or not to simulate. What is the question? Ann Surg. 2006;243:301–303 Wu J, Wang H, Zhang P, Ma X, Hu Q. A preliminary real-time and realistic simulation environment for percutaneous coronary intervention. BioMed Res Int 2015 . 2015:Article number 183157